PENATAAN SARANA DAN PRASARANA DALAM PERKEMBANGAN ANAK DI SEKOLAH: ARRANGEMENT OF FACILITIES AND INFRASTRUCTURE IN CHILD DEVELOPMENT AT SCHOOL - Rieuwpassa, Nazwa (Thufuli, 2024)
This study focusses into how school infrastructure and facilities affect the general growth of children. Specifically, academic and non-academic factors are topic of this research. The purpose of this study is to explain how children's academic performance, social skills, and emotions are impacted by in good condition spaces especially classrooms, libraries, and recreation areas. Using a descriptive qualitative literature review methodology, this study methodically analyses information from present research papers. The analysis's findings show that: 1) Three (three) key principles need to be followed while arranging infrastructure and facilities. 2) High- quality facilities and infrastructure affect children's academic performance and 3) their non-academic performance. It recommended that future studies analyse the specific impacts of different types of facilities and how they contribute to greater educational equality.